A size independent enriched finite element for the modeling of bimaterial interface cracks. (August 2016) - Hu, X.F.; Wang, J.N.; Yao, W.A.
Highlights: An enriched element is proposed for bimaterial interface cracks under combined plane and antiplane deformation. Higher order eigen expanding terms are adopted to enrich the proposed element. The element's stiffness matrices for both plane and antiplane deformations are found to be independent of the its size. Mixed mode (I/II/III) stress intensity factors can be calculated accurately without post-processing. Abstract: The failure of structures made of multiple materials is often caused by bimaterial interface cracks. Due to the complex nature of the stress field around the interface crack tip, the faithful modeling of such cracks requires numerical methods with high accuracy and stability. For this purpose, an enriched element is proposed in this study. The element's interior fields are described only by using the Williams eigen solutions. The element's stiffness matrices for both plane and antiplane deformations are proven to be independent of its size, and the fracture parameters can be obtained accurately for a wide range of mesh densities.